Energy Optimization of Routing Protocols in Wireless Sensor Networks - Fatima Es-sabery; Hicham Ouchitachen; Abdellatif Hair (Institute of Advanced Engineering and Science, 2017)
The hierarchical routing of data in WSNs is a specific class of routing protocols it encompasses solutions that take a restructuring of the physical network in a logical hierarchy system for the optimization of the consum-ption of energy. Several hierarchical routing solutions proposed, namely: the protocol LEACH (Low Energy Adaptive Clustering Hierarchy) consist of dividing the network in distributed clusters at one pop in order of faster data delivery and PEGASIS protocol (Power-Efficient Gathering in Sensor Information Systems) which uses the principle of constructing a chain’s sensor node. Our contribution consists of a hierarchical routing protocol, which is the minimization of the energy consumption by reducing the transmission distance of data and reducing the data delivery time. Our solution combines the two hierarchical routing approaches: chain based approach and the cluster based approach. Our approach allows for multi-hop communications, intra- and intercluster, and a collaborative aggregation of data in each Cluster, and a collaborative aggregation of data at each sensor node.